2020
DOI: 10.1111/aos.14621
|View full text |Cite
|
Sign up to set email alerts
|

The impact of structural optical coherence tomography changes on visual function in retinal vein occlusion

Abstract: Purpose We aimed to determine the correlation between optical coherence tomography (OCT)‐ and demographic features and baseline best corrected visual acuity (BCVA) in treatment‐naïve patients with retinal vein occlusion (RVO). Methods This was a cross‐sectional posthoc analysis of OCT images that included RVO patients from two prospective, open‐label, multicentre studies. The morphological grading was done manually, in the standardized setting of a reading centre. Main outcome measure was the estimated differe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 50 publications
0
7
0
Order By: Relevance
“…In particular, previous studies identified the correction of disruption in the OLM with poor visual prognosis after RVO treatment [29][30][31][32]. However, in a recent study that collected and analyzed the data of 381/301 BRVO/CRVO naive patients from the BRIGHTER and CRYSTAL studies, only 5 Computational and Mathematical Methods in Medicine CRT and age were associated with visual prognosis instead of OLM disruption or DRIL [15]. In our study, we noted a significant correlation between baseline OLM disruption at the fovea and ME recurrence, suggesting that baseline OLM integrity could serve as a predictor for recurrence of ME.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…In particular, previous studies identified the correction of disruption in the OLM with poor visual prognosis after RVO treatment [29][30][31][32]. However, in a recent study that collected and analyzed the data of 381/301 BRVO/CRVO naive patients from the BRIGHTER and CRYSTAL studies, only 5 Computational and Mathematical Methods in Medicine CRT and age were associated with visual prognosis instead of OLM disruption or DRIL [15]. In our study, we noted a significant correlation between baseline OLM disruption at the fovea and ME recurrence, suggesting that baseline OLM integrity could serve as a predictor for recurrence of ME.…”
Section: Discussionmentioning
confidence: 98%
“…Furthermore, central retinal thickness (CRT) is a measure derived from OCT scans and is an essential outcome in clinical trials to assess drug efficacy and vision outcomes [13]. Previous studies have identified the corrections between CRT and visual outcomes after administration of anti-VEGF therapy in patients with ME due to RVO [14,15].…”
Section: Introductionmentioning
confidence: 99%
“…In retinal vein occlusion, HRF were topographically scattered along the OPL and the external limiting membrane [103,105]. Similar to other retinal diseases, a poor visual outcome after anti-VEGF treatment accompanied the identification of HRF at baseline [104,106]. Furthermore, the use of intravitreal DEX implants might be privileged in eyes with numerous HRF and long-standing macular edema secondary to RVO in consideration with the inflammatory component [107].…”
Section: Miscellaneousmentioning
confidence: 96%
“…Our findings have been published in an abstract for the European Society of Retina Specialists (EURETINA). 6 Although the qualitative approach to DRIL assessment in the present study is a practical solution, the use of quantitative measurements, such as DRIL length or area, might yield additional information in terms of the structural evolution of the feature. With ischemia being a main driver of sequelae in RVO, functional and structural reversibility is of great importance.…”
mentioning
confidence: 93%